The Influence of Magnetic Media Usage on Improving Reading Literacy Skills in Material Understanding of Objects in Second Grade Elementary School - Ana Fitria; Wati Sukmawati (Postgraduate, University of Mataram, 2024)
This study explores the effectiveness of magnetic media in enhancing students' literacy skills in material state changes. Traditional teaching methods often struggle to effectively convey abstract scientific concepts, resulting in varying student performance levels. To address this gap, magnetic media was introduced as an interactive visual aid in the learning process. The study employed a pretest-posttest design with students from a science class, analyzing their literacy skills before and after using magnetic media. Results showed an average pretest score of -5.481, improving to -4.771 in the posttest, indicating a significant average increase of 0.71 points. Posttest scores also exhibited lower standard deviations, suggesting more consistent performance among students. This underscores that magnetic media supports both high and low-achieving students, promoting a more uniform understanding across different performance levels. Such inclusivity is crucial in education to ensure effective teaching methods for diverse learners. The study contributes by highlighting the unique benefits of magnetic media in providing tangible and visual representations of abstract concepts. Future research should further explore its application in different educational contexts and optimize strategies to maximize its benefits in teaching and learning.